Synergistic mechanism of supported Mn–Ce oxide in catalytic ozonation of nitrofurazone wastewater. (December 2022) - Ma, Nengwei; Ru, Yifan; Weng, Mili; Chen, Lu; Chen, Wenqing; Dai, Qizhou
Abstract: In this study, the catalytic materials of MnOx /γ-Al2 O3, CeO2 /γ-Al2 O3, and Mnx Ce1-x O2 /γ-Al2 O3 for catalytic ozonation were synthesized. The catalysts were used in heterogeneous catalytic ozonation of the wastewater containing ntrofurazone (NFZ). The effects of the catalytic ozonation operational factors were systematically evaluated in terms of ozone dosing, catalyst dosing, initial NFZ concentration, and pH. The results showed that the catalytic activity of the Mnx Ce1-x O2 /γ-Al2 O3 was higher than that of the MnOx /γ-Al2 O3 and CeO2 /γ-Al2 O3 . The kinetics analysis revealed that bimetallic loading has a synergistic effect and the mechanism of this effect was investigated in the catalytic ozonation system. The catalysts were characterized by FESEM, EDS, XRD, XPS, IR, and BET. The characteristics of the catalysts revealed that Mn could alter the oxide species on the metal surface and interfere with the formation of CeO2 crystals, which led to smaller grains, enhanced adsorption oxygen, and greater specific surface area. The Mnx Ce1-x O2 /γ-Al2 O3 crystals could form a solid solution, which helps higher catalytic activity. This study adds to the understanding of the synergistic mechanism of the loaded Ce–Mn oxide catalysts in the heterogeneous catalytic ozonation system and provides a feasible method for degrading pharmaceutical wastewater. Graphical abstract: Image 1 Highlights: A loaded Mnx Ce1-x O2 /γ-Al2 O3 catalyst for catalytic ozonation was synthesized. The synergistic effect of catalytic ozonation degradation of NFZ was investigated. The synergistic catalytic mechanism of Mnx Ce1-x O2 /γ-Al2 O3 was explored.